Children's Representations of Attachment and Positive Teacher–Child Relationships - Veríssimo, Manuela; Torres, Nuno; Silva, Filipa; Fernandes, Carla; Vaughn, Brian E.; Santos, António J. (Frontiers in Psychology, 2017)
This study was designed to explore whether children’s representations of attachment contribute to the co-construction of positive teacher-child relationships. An assessment of verbal intelligence was included as a predictor on the assumption that teachers might perceive themselves as having better relationships with more verbally competent children. Participants were 52 children from two pre-schools, in the district of Lisbon. The Attachment Story Completion Task (ASCT) was used to assess children’s attachment security. The PCV-P (a scale developed in portuguese language) was used to describe teacher-child relationships through teachers’ ratings of child secure base behavior and emotion regulation and the Wechsler Preschool and Primary Scale of Intelligence (WPPSI-R) was used to access verbal skills. Bivariate correlations showed that the teachers’ rating of child secure base behavior was significantly associated with both child attachment security and verbal IQ. In a multiple regression analysis, the overall model R2 was significant, as was the interaction term showing a moderating effect of attachment security on the relation between verbal IQ and teachers’ ratings of secure base. The results suggest that co-construction of a close attachment-relevant relationship with teachers in early childhood is, in part, a function of the security in the context of parent-child attachment, but also of child verbal development.